Given,
![\begin{gathered} \text{The system of pair of linear equation is,} \\ 18x-10y=74\ldots\ldots\ldots\ldots\ldots.\ldots.(i) \\ 9x-9y=45\ldots\ldots\ldots..\ldots\ldots\ldots.(ii) \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/ighd697mwa79v3bg2c2xepsllxc5askkoa.png)
Multiplying equation (ii) by 2 as it make the coefficent of x in both equation equal.
![\begin{gathered} 18x-10y=74\ldots\ldots\ldots\ldots\ldots.\ldots.(i) \\ 18x-18y=90\ldots\ldots\ldots..\ldots\ldots\ldots.(iii) \\ \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/4iq2imzhm9sletqm6ylcxkaq5c3bloqalc.png)
Substracting equation (i) from equation (iii) then we get,
![\begin{gathered} 18x-18y-(18x-10y)=90-74 \\ 18x-18y-18x+10y=16 \\ -8y=16 \\ y=-2 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/q814b3up8sn3gtngenq2uafivohv7518jz.png)
The value of y is -2.
Substituting the value of y in equation (i) then,
![\begin{gathered} 18x-10y=74 \\ 18x+20=74 \\ 18x=54 \\ x=3 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/surso8jh28woe2uvb260h6lg12f8fi86il.png)
Hence, the solution of the linear pair (x, y) is (3, -2).